Strengthening the National Identity of Indonesian Children Abroad through an Educational Program on Indonesian Islands and Culture - Usmaidar Usmaidar; Rosalinda Rosalinda; Rika Anggraini (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to enhance knowledge, foster a sense of patriotism, and strengthen the national identity of Indonesian children living abroad through an educational program introducing Indonesian islands and culture. Children living in foreign environments tend to interact more frequently with foreign cultures, potentially leading to a lack of familiarity with their own national culture. Therefore, this activity was designed as a fun and easily understandable learning experience to ensure children remain connected to their roots. The method used was qualitative descriptive research employing direct observation of 30–40 participants over a two-week period. The program was implemented in several stages: orientation, presentation of materials, video screenings, drawing and coloring activities, and traditional games. The results showed that participants demonstrated increased knowledge of the names of major islands in Indonesia as well as various regional cultures, such as traditional attire, dances, and folk songs. Additionally, the program successfully fostered a sense of pride, boosted self-confidence, and strengthened camaraderie among participants. The children appeared enthusiastic and active in every activity provided. Thus, this educational program proved effective as a means to introduce Indonesian culture while strengthening the national identity of Indonesian children abroad through engaging and enjoyable learning methods.